2015
DOI: 10.1177/1076029615614395
|View full text |Cite
|
Sign up to set email alerts
|

PRescriptiOn PattERns of Oral Anticoagulants in Nonvalvular Atrial Fibrillation (PROPER study)

Abstract: Inappropriate drug use is frequent among patients with NVAF not only for warfarin but also for NOACs. Although there is an apparent improvement in thromboprophylaxis of NVAF, much more effort is needed for appropriate use of OACs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 26 publications
4
44
1
1
Order By: Relevance
“…Earlier study evaluating prescription patterns of oral anticoagulants (OAC) found up to 47% of off-label use of NOACs. [8] Similarly, in a study conducted in Danish population, high prevalence of off-label prescription of dabigatran was noticed. [9] The misuse of NOACs indicated by the real-world data could be a possible reason for the adverse events.…”
Section: Introductionmentioning
confidence: 91%
“…Earlier study evaluating prescription patterns of oral anticoagulants (OAC) found up to 47% of off-label use of NOACs. [8] Similarly, in a study conducted in Danish population, high prevalence of off-label prescription of dabigatran was noticed. [9] The misuse of NOACs indicated by the real-world data could be a possible reason for the adverse events.…”
Section: Introductionmentioning
confidence: 91%
“…(C) Real‐world studies results concerning dose adjustments of apixaban. (D) Results from direct oral anticoagulants overall adjustments regarding dose appropriateness…”
Section: Resultsmentioning
confidence: 99%
“…Canadian study, 44 where a total of 47 patients were included, among (D) Results from direct oral anticoagulants overall adjustments regarding dose appropriateness 5,9,11,25,27,28,32,34,37,39,40,42,44,[47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64] whom 25 (53%) were receiving apixaban inconsistent with the ARIS-TOTLE trial and the product monograph.…”
Section: Study and Also By A Smallmentioning
confidence: 99%
“…In a single-center study of 148 patients, rivaroxaban was found to be dosed inappropriately according to the Medication Appropriateness Index in 23% of patients vs. 42% and 81% of patients on dabigatran and warfarin, respectively 6 . This may suggest that simpler dosing adjustment criteria may lead to less inappropriate dosing with oral anticoagulants.…”
Section: Discussionmentioning
confidence: 99%